The psychology of youth knife crime - Jareno Ripoll, Sandra; Browne, Kevin; Green, Kathleen; Paddock, Elizabeth (2024)
Knife crime continues to be a prevalent crime type affecting children and young people in the UK. It has been highlighted that there are large gaps and limitations within knife crime research literature, which makes it difficult to draw strong conclusions about what works to reduce knife crime.